Criminal Liability for Bankrupt Foreign Debtors in Indonesia - Butarbutar*, Russel; Sianturi, Martunas (Riwayat: Educational Journal of History and Humanities, 2023)
This research aims to determine the means of criminal liability that can be applied to bankrupt foreign debtors in Indonesia. This research was carried out normatively by referring to the Commercial Court decision in accordance with Decision Number 11/Pdt.Sus-PKPU/2018/PN.Niaga Mdn. Criminal liability for bankrupt foreign debtors who do not act in good faith in implementing court decisions and/or assisting the Curator to carry out their duties in accordance with statutory regulations can be criminally prosecuted, in the form of: (1) the crime of embezzlement as regulated in Article 372 of the Criminal Code; (2) Criminal action against a person who does not carry out a court order (decision) because this action could be considered an action that obstructs an order from an official or public authority (contempt of court) as regulated in Article 216 paragraph (1) of the Criminal Code; (3) Criminal acts of fraud by Bankrupt Debtors against Creditors as regulated in Article 400 of the Criminal Code concerning; (4) The criminal act of alienating the debtor's assets to the detriment of his creditors as regulated in Article 397 of the Criminal Code; (5) The crime of forgery of documents as regulated in Article 263 in conjunction with Article 264 of the Criminal Code